El camino precolombino del Sitio Arqueológico Alto del Cardal C-304 AC - Cavallini Morales, Carolina (2012)
The archaeological site Alto del Cardal C-304 AC has a road that was used in ancient times to access to the Caribbean in less time according to accounts of previous investigators who visited the area and residents. Recent research determined the possible route of the road.